P5.103 Increase of African-Type Penicillinase-Producing N. Gonorrhoeae Strains Isolated in Guangzhou, China, 2001–2011. (13th July 2013) - Zheng, H; Yang, B; Wu, X; Qin, X; Huang, J; Xue, Y; Zeng, W; Ou, J; Lan, Y; Tang, S
Abstract : Background: The continuing spread of drug-resistant gonococci has posed a challenge for successful treatment worldwide. Guangdong Province in South China has one of the highest resistance rates of gonococci in China and a large number of international migrants. We investigated the in vitro antimicrobial susceptibility and genotypes of N. gonorrhoeae isolated in Guangzhou, the capital city, in 2001–11. Methods: MICs to penicillin, ceftriaxone, tetracycline, ciprofloxacin, and spectinomycin were determined by agar plate dilution and susceptibilities were interpreted according to WHO standards. Penicillinase-producing N. gonorrhoeae (PPNG) was determined by paper acidometric testing and high-level tetracycline resistant N. gonorrhoeae (TRNG) by MIC. The isolates with resistant plasmids were genotyped by PCR. Results: Of 1250 consecutive gonococci isolated during 2001–11, no ceftriaxone and spectinomycin resistant strains were found, but the prevalence of less susceptible strains to ceftriaxone rose from 17% to 46.5%. The MIC90 for ceftriaxone showed intermediate sensitivity (0.06–0.125µg/mL) and spectinomycin near the resistant level (16–32µg/mL). The resistance to penicillin, tetracycline and ciprofloxacin were from 85%, 85% and 78% in 2001 to 81.9%, 100% and 98.4% in 2011, respectively. Of 349 (27.9%) PPNG and 539 (43.1%) TRNG detected. 232 (18.6%) strains were both PPNG and TRNG. PPNG increased from 17.0% to 32.3% and TRNG from 26.0% to 41.7% during 2001–10. Genotyping TEM-1 gene showed 94.8% PPNGs carrying the Asia-type β-lactamase plasmids. The Africa-type PPNG (1, 1.3%) emerged in 2008 and has increased to 8(6.2%) in 2011. Genotyping of tetM gene showed all TRNGs were Dutch variants. Conclusion: Gonorrhea resistance continues to be a major public health problem in Guangzhou. The emergence and increase of African-type PPNG may be related to the large African diasporas in Guangzhou, migration of Chinese to Africa, or other migration patterns. More research is needed to determine what practises, systems and behaviours contribute to escalating resistance patterns.